Profitability of diammonium phosphate use in bush and climbing bean-maize rotations in smallholder farms of Central Burundi - Niyuhire, M.C.; Pypers, Pieter; Vanlauwe, Bernard; Nziguheba, Generose; Roobroeck, D.; Merckx, Roel (Elsevier, 2017)
Soil fertility decline is a major constraint to bean (Phaseolus vulgaris L.) and maize (Zea mays) production in the Central Highlands of Burundi. Nutrient sources, specifically fertilizers, are paramount to increasing the production in the regions. Hence, improving fertilizer use efficiency is considered as a key factor towards sustainable intensification. The use of grain legumes with low harvest indices, such as climbing beans, are assumed to improve soil fertility and fertilizer use efficiency. This study compares the rotational effects of bush and climbing bean varieties on maize and evaluates the profitability of diammonium phosphate (DAP, 18–46-0) fertilizer in the bean-maize rotations in 59 smallholder farms of Mutaho district, Gitega Province in Central Burundi. The application of DAP fertilizer significantly increased the grain yields by 14% and 21% for bush and climbing beans, respectively (P < 0.001). Positive effects of bean varieties were large for about 80% of the farmers. Climbing beans in general yielded more than bush beans for about two thirds of the farmers and fertilizer effects were positive. In the bean-maize rotations, the fertilizer induced on average a yield increase of 8% and 22% for maize following bush and climbing beans, respectively. Maize grain yields were significantly (P < 0.001) higher following climbing beans than following bush beans. The value cost ratio (VCR) more than doubled compared with the common practice (bush bean-maize rotation). Variation was substantial, and for approximately 67% of the farmers, DAP application was profitable (VCR > 2 $ $−1) in a climbing bean-maize rotation while 45% of the farmers in a bush bean-maize rotation. Regression tree analysis showed that targeting fertilizer use to soils with higher C and clay content, and ensuring timely planting are the predominant factors to ensure fertilizer response and profitable returns. This study confirms the need for integrated soil fertility management (ISFM), and that a combination of judicious fertilizer use, an improved grain legume (climbing bean) and adjustment to local conditions (targeting to responsive soils) maximizes economic returns of legume-cereal rotation systems.